"I'll Pencil You In" — The Overscheduled Child - Jodimae Lyttle; Eboni J. Baugh (EDIS)
FCS-2285, a 3-page fact sheet by Jodimae Lyttle and Eboni J. Baugh, describes for parents the consequences of over-scheduling a child and provides tips for keeping a child active but not overscheduled. Includes references. Published by the UF Department of Family Youth and Community Sciences, August 2008.